What Gender Does: Decertification of Legal Gender in India - Varman, Nipuna (feminists@law, 2022)
This article explores the implications of decertification of legal gender in the Indian context, with a particular focus on the religious sphere. It explores the discourse on gender as it currently exists in India and suggests that imagining a future with no legal gender is a fruitful exercise. The article looks at the conception of gender as property to explore how recognition is granted to such property. It argues that the absolute withdrawal of the State from the sphere of gender may lead to persons being forced to conform to social conceptions of gender. Therefore, it differentiates between the idea of decertification and gender blindness of the State. Additionally, it argues for an approach to the idea of property that does not isolate it but recognises the ideas of interdependency, relational autonomy and non-domination. The effect of decertification on religious institutions in India is firstly understood based on the extent of State control over religion and religious institutions. The article observes that in the Indian context the relationship between the State and religion is to some extent unclear. However, the decertification exercise will make the gendered construction of religious laws difficult to maintain, especially the codified religious laws.